Vulvodynia: Pain Management Strategies - Lucia Merlino; Luca Titi; Francesco Pugliese; Giulia D'Ovidio; Roberto Senatori; Carlo Della Rocca; Maria Grazia Piccioni (MDPI AG, 2022)
Background: Vulvodynia is defined in this international consensus as persistent vulvar pain that occurs for >3 months without an identifiable cause and with several potential associated factors. At present there is no univocal consensus in the therapeutic treatment of vulvodynia. The methods of intervention are based on various aspects including, above all, the management of painful symptoms. Methods: a research on scientific database such as "Pubmed", "Medline Plus", "Medscape" was conducted, using the words "women's genital pain" and "vulvodynia" for the review of the scientific evidence on the assessment and treatment of women's genital pain. Results: Among the drugs with pain-relieving action, the most effective in the treatment of vulvodynia would seem to be those with antidepressant and anticonvulsant action, even if their mechanisms of action are not known and there are still insufficient studies able to demonstrate their real validity. Among the least effective are non-steroidal anti-inflammatory drugs (NSAIDs) and corticosteroids. However, the ideal would seem to use a combined treatment with multiple types of drugs. Conclusions: Future studies are needed to draw up a unique therapeutic action plan that considers the stratification of patients with vulvodynia and the variability of the symptom.